2011
DOI: 10.3390/cryst1030099
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Na3MoCl6

Abstract: Abstract:The ternary chloride Na 3 MoCl 6 is obtained as red crystals from a disproportionation reaction of molybdenum dichloride, {Mo 6 }Cl 12 , in an acidic NaCl/AlCl 3 melt at 350 °C. The crystal structure (trigonal, P-31c, a = 687.1(1), c = 1225.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous experimental studies revealed that Na 3 MCl 6 with relatively small M cations, for instance, V, Cr, or Mo, adopts the trigonal P 3̅1 c phase, while compositions with moderate M cations, for example, Sc, Ti, Y, and the lanthanides Dy–Lu, exhibit the monoclinic P 2 1 / n structure and turn to trigonal R 3̅ phases as the radii of M cations further increase. These findings were confirmed by Yu’s theoretical work which was mentioned earlier .…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental studies revealed that Na 3 MCl 6 with relatively small M cations, for instance, V, Cr, or Mo, adopts the trigonal P 3̅1 c phase, while compositions with moderate M cations, for example, Sc, Ti, Y, and the lanthanides Dy–Lu, exhibit the monoclinic P 2 1 / n structure and turn to trigonal R 3̅ phases as the radii of M cations further increase. These findings were confirmed by Yu’s theoretical work which was mentioned earlier .…”
Section: Resultsmentioning
confidence: 99%
“…The simulation cells of sodium halides Na 3 MX 6 (X = Cl, Br and I) were generated based on the experimental structures of Na 3 MX 6 that exhibited trigonal P 3̄1 c (#163), 49,50 monoclinic P 2 1 / n (#14), 34,35 trigonal R 3̄ (#148) 51 and monoclinic C 2/ m (#12) 29 crystal structures. The trigonal P 3̄ m 1 (#164) Li chloride structure, Li 3 MX 6 , 27 was also used to prepare Na 3 MX 6 simulation cells.…”
Section: Methodsmentioning
confidence: 99%